2011
DOI: 10.3390/rs3081777
|View full text |Cite
|
Sign up to set email alerts
|

Segment-Based Land Cover Mapping of a Suburban Area—Comparison of High-Resolution Remotely Sensed Datasets Using Classification Trees and Test Field Points

Abstract: Abstract:In order to better understand and exploit the rich information content of new remotely sensed datasets, there is a need for comparative land cover classification studies. In this study, the automatic classification of a suburban area was investigated by using (1) digital aerial image data; (2) digital aerial image data and laser scanner data; (3) a high-resolution optical QuickBird satellite image; (4) high-resolution airborne synthetic aperture radar (SAR) data; and (5) SAR data and laser scanner dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Table 3 shows a comparison with similar works that have done per-pixel classification estimation with similar choices of categories, but that cover other land areas. A direct comparison of different studies is not possible, because of different study areas, data acquisition methods and resolutions, reference datasets and class definitions [48]. However, it can be concluded that the use of CNNs for per-pixel classification is capable of achieving comparable results to the typically-regarded state-of-the-art object-based image analysis (OBIA) methods.…”
Section: Classification Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows a comparison with similar works that have done per-pixel classification estimation with similar choices of categories, but that cover other land areas. A direct comparison of different studies is not possible, because of different study areas, data acquisition methods and resolutions, reference datasets and class definitions [48]. However, it can be concluded that the use of CNNs for per-pixel classification is capable of achieving comparable results to the typically-regarded state-of-the-art object-based image analysis (OBIA) methods.…”
Section: Classification Resultsmentioning
confidence: 99%
“…Furthermore, a DSM is invariant to lighting and color variations and can give a better geometry estimation and background separation [48]. However, the measurements in a DSM need to be normalized because they are measured from a global reference point and not from the local surrounding ground level.…”
Section: Data and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is a point inside a segment, the entire segment is assumed to belong to the class defined by the point. This approach is flexible and allows the same point set to be applied to different images and segmentations (Matikainen and Karila, 2011).…”
Section: Methods For Change Detectionmentioning
confidence: 99%
“…Impervious land cover have similar spectral properties especially when only limited number of bands were used; therefore, inclusion of spatial and texture information into urban area classification is necessary (Salehi;2012) Different researchers have applied various approaches to improve urban land use/cover accuracy with the inclusion of geographic data, textural features, contextual information, expert systems and fuzzy classification (Thapa and Murayama, 2009;Deng et al, 2009;Weng, 2012;Mohapatra, and Wu, 2011;Lu, and Weng, 2006;City Development Information. , 2014;Gamba et al, 2005;Matikainen and Karila, 2011). The importance of different requirements for spatial, spectral and temporal resolution and geometric characteristics of urban features to map impervious surfaces in the urban areas using remotely sensed data was emphasized (Herold et al, 2003).…”
Section: Introductionmentioning
confidence: 99%